Bob Marley : Rebel Music - Jeremy Marre; Rita Marley (USA UK Palm Pictures, 2000)
The legend of Bob Marley (1945-1981) is well served by this comprehensive and clear-eyed look at the turbulent life and times of the reggae great. Jeremy Marre's documentary presents the man as a vitally important artist, but a flawed--if immensely appealing--human being. The trajectory of his rise is traced from his humble beginnings as the son of a poor, teenage mother in rural Jamaica to the heights of international superstardom in the 1970s. Along the way, Marre provides a context for the development of his artistry by exploring the political situation in Jamaica at the time, the roots of Rastafarianism (to which he was intensely devoted), and his unconventional relationships with women. Although he remained close to wife, Rita, until his death, Marley enjoyed a number of public relationships with other women (Rita admits she found this difficult; Marley claims he didn't see anything unusual about it). The sheer number of interviews is impressive. Aside from the clips of Marley himself, Bunny Livingstone and Peter Tosh (the Wailers), Island Records founder Chris Blackwell, two Jamaican prime ministers (Socialist Michael Manley and Conservative Edward Seaga), and even a CIA official (Philip Agee) all make an appearance. The breadth of Marley's music is represented by over 40 tracks, from the early ska hit "Judge Not" to later political numbers like "Africa Unite." Although Marley never actually considered himself a "political" person, he was surely a rebel--brave, passionate, committed--in the best sense of the word.
Profile of the life and music of the legendary reggae singer.
Language : English Subtitles : English, German, French, Spanish, Italian
Keywords: Music; Documentary